Protocol for Japan-acute retinal necrosis (J-ARN) registry: A combined prospective and retrospective cohort study. - Yoshihiko Usui; Reiko Kinouchi; Satoko Nakano; Chiharu Iwahashi; Keitaro Hase; Kenji Nagata; Masahiro Sugimoto; Eiichi Hasegawa; Kinya Tsubota; Sentaro Kusuhara; Masato Akiyama; Kenji Kashiwagi; et al. (PLoS ONE)
Background Acute retinal necrosis (ARN) is a rare but vision-threatening viral retinitis that can lead to severe visual impairment or blindness if not diagnosed and treated promptly. However, due to its rarity, there are limited large-scale data on the clinical characteristics, treatment approaches, and outcomes of ARN in Japan. A nationwide registry is needed to systematically collect data on ARN cases across Japan to improve understanding of this condition and optimize patient care. We have designed a national registry that collects data of patient characteristics, diagnosis, treatment, and visual outcome to generate evidence for the management of ARN. Methods and design This research is a combined retrospective and prospective, multicenter cohort study of ARN in Japan from 1 April 2014-31 March 2029 (UMIN000056246). The registry has received Japan-wide approval from a national human research ethics committee. The following data will be collected: patient demographics, visual function at the initial visit and 6, 12, 24, and 36 months later, image data, diagnostic methods, virus analysis, indications and timing of vitrectomy, and complications. Customized software and platforms have been designed to permit data collection for a single baseline and multiple follow-up forms. Discussion By analyzing the accumulated patient information, the results of this study will generate real-world evidence that will contribute to solve various important clinical issues in ARN. The results will be presented after data collection and analysis are completed.